Dying and Grieving / Life Span and Family Perspectives - Oltjenbruns Kevin Ann; Skinner Cook Alicia (Harcourt Brace College Publishers, 1998)
Preface, Foundations of a Holistic Developmental Model, Death and Grief in Contemporary Society, The Dying Individual, Grief and Loss, The Bereaved Family, Developmental Perspectives on Dying and Grieving, Dying and Grieving Children, Death and Gief During Adolescence, Facing Death as an Adult, Grief and Loss During Adulthood, Suicide, Implications for Caregivers, Issues for Professional Caregivers, Photo Credits, Subject and Author Index.